P-766 Birth outcomes in Anti-centromere antibody (ACA) -positive patients treated with ART. (30th June 2022) - Kida, Y; Tokoro, M; Kitasaka, H; Yoshimura, T; Fukunaga, N; Asada, Y
Abstract: Study question: Does the presence of the ACA have any effect on pregnancy and birth? Summary answer: Presence of ACA did not have an impact on pregnancy and birth parameters measured. What is known already: We have previously shown that patients with high levels of anti-centromere antibody (ACA), one of the anti-nuclear antibodies (ANA), frequently have dispersion of chromosomes in the cytoplasm. Additionally, we reported that it was characterized by a low oocyte maturation rate as observed at ovum pick up, high multiple pronuclear formation after fertilization and a low pregnancy rate after embryo transfer. Thus, the effect of ACA on fertility is clear, but the impact following pregnancy establishment has not yet been reported. Therefore, we followed up on birth outcomes in ACA-positive patients treated with ART. Study design, size, duration: 3379 patients who underwent ANA testing followed by embryo transfer between January 2014 and February 2020 and who gave birth including the results of single births with no abnormal or missing values for week and birth weight were analyzed. The subjects were classified into three groups: ANA-negative (without ACA or any other ANA), ACA-positive (with only ACA) and ANA-positive (with ANA but not ACA). Participants/materials, setting, methods: We compared mean birth weight (full term), low weight birth infant (less than 2, 500g) rate, sex ratio, congenital anomaly rate, preterm birth rate, cesarean section rate, and mean apgar score (AP) in the three groups. We treated "don't know" and "blank" for items other than week and birth weight as non-responses and missing values. Main results and the role of chance: Of the 3379 cases for analysis, the group numbers were ANA-: 2465, ACA+: 21, ANA+: 893. The mean birth weights were 3099.6g, 3055.3g and 3088.5g respectively. In the 3 groups the rate of low birth weight infants were 8.7% (215/2465), 9.5% (2/21) and 9.2% (82/893), the sex ratio (male/female)-1.03 (1246/1212), 0.62 (8/13) and 0.93 (429/ 460), congenital anomaly rate 2.7% (67/2465), 4.8% (1/21), 3.2% (29/893), preterm birth rate 7.4% (86/2465), 4.8% (1/12), 6.7% (60/893), cesarean rate 40.0% (979/2448), 42.9% (9/21), 41.3% (367/888), and mean AP was 8.3, 8.2, and 8.3 respectively. There was no significant difference between the three groups in any of the measured items. Limitations, reasons for caution: This study was conducted at a single institution, and only the results of those who responded to the birth survey questionnaire were analyzed. Because of the small number of patients in the ACA group, continued follow-up is considered necessary. Wider implications of the findings: It was shown that ACA strongly affects maternal fertility, but seems to have no effect on birth parameters. However we will continue to follow up with further long-term prognostic studies. Trial registration number: not applicable